HOW DO MEDIA NARRATIVES FRAME INCLUSIVE GOVERNANCE IN INDONESIA'S CHILD-FRIENDLY CITIES? A CORPUS-DISCOURSE ANALYSIS - Sajida Sajida; Ismi Dwi Astuti Nurhaeni; Sri Yuliani; Rina Herlina Haryanti; Asal Wahyudi Erlin Mulyadi (Universitas Negeri Yogyakarta, 2025)
Inclusive governance typically denotes an ethical framework that assures jointly, participatory, and culturally sensitive policy-making, especially in the execution of urban child protection initiatives. This research digs into and discusses the public discourse around the Indonesian Kota Layak Anak (Child-Friendly City/KLA) policy, examining the different media narratives on how they emancipate, legitimize, obfuscate, or thwart the principles of inclusive governance. By using a corpus-assisted discourse analysis (CADS) method, the authors carry out an analysis of 136 articles from different national and local media that were published between 2011 and 2025, and talk about the KLA implementation in Surakarta. The analysis operationalizes inclusive governance along system (collaborative, multi-level governance), actor (accountability, deliberative participation), and culture (community-driven governance) dimensions. The findings reveal that community narratives and cultural narratives prevail discursively and that these heavily draw on local traditions, communal involvement, and symbolic activities. Conversely, accountability and institutional collaboration are practically absent from media scrutiny, often mentioned in passing or in gratuitous terms. The media appears to portray KLA more as a ceremonial success rather than an arena for structural policy reform. The article proposes a discourse analysis framework for understanding how these narratives support or undermine inclusive governance. The study thus contributes to the literature of governance evaluation, policy framing, and discourse analysis by designing a replicable method to assess how the public narration mirrors or masks multi-actor urban policy realities.